The Position of His-Tag in Recombinant OspC and Application of Various Adjuvants Affects the Intensity and Quality of Specific Antibody Response after Immunization of Experimental Mice - Krupka, Michal; Masek, Josef; Barkocziova, Lucia; Turanek Knotigova, Pavlina; Kulich, Pavel; Plockova, Jana; Lukac, Robert; Bartheldyova, Eliska; Koudelka, Stepan; Chaloupkova, Radka; Sebela, Marek; Zyka, Daniel; et al. (PloS one, 2016)
Lyme disease, Borrelia burgdorferi-caused infection, if not recognized and appropriately treated by antibiotics, may lead to chronic complications, thus stressing the need for protective vaccine development. The immune protection is mediated by phagocytic cells and by Borrelia-specific complement-activating antibodies, associated with the Th1 immune response. Surface antigen OspC is involved in Borrelia spreading through the host body. Previously we reported that recombinant histidine tagged (His-tag) OspC (rOspC) could be attached onto liposome surfaces by metallochelation. Here we report that levels of OspC-specific antibodies vary substantially depending upon whether rOspC possesses an N' or C' terminal His-tag. This is the case in mice immunized: (a) with rOspC proteoliposomes containing adjuvants MPLA or non-pyrogenic MDP analogue MT06; (b) with free rOspC and Montanide PET GEL A; (c) with free rOspC and alum; or (d) with adjuvant-free rOspC. Stronger responses are noted with all N'-terminal His-tag rOspC formulations. OspC-specific Th1-type antibodies predominate post-immunization with rOspC proteoliposomes formulated with MPLA or MT06 adjuvants. Further analyses confirmed that the structural features of soluble N' and C' terminal His-tag rOspC and respective rOspC proteoliposomes are similar including their thermal stabilities at physiological temperatures. On the other hand, a change in the position of the rOspC His-tag from N' to C' terminal appears to affect substantially the immunogenicity of rOspC arguably due to steric hindrance of OspC epitopes by the C' terminal His-tag itself and not due to differences in overall conformations induced by changes in the His-tag position in rOspC variants.
Keywords: imunizace; Models, Animal; Protein Stability; Antibodies, Bacterial; Recombinant Fusion Proteins; Borrelia burgdorferi; lymeská nemoc; stabilita proteinů; Bacterial Outer Membrane Proteins; Lyme Disease; proteolipidy; Proteolipids; sekundární struktura proteinů; rekombinantní fúzní proteiny; Protein Structure, Secondary; ELISA; antigeny bakteriální; Adjuvants, Immunologic; Enzyme-Linked Immunosorbent Assay; Animals; Antibody Specificity; specificita protilátek; adjuvancia imunologická; zvířata; tvorba protilátek; myši; protilátky bakteriální; modely u zvířat; Antigens, Bacterial; Antibody Formation; Mice; Immunization; proteiny vnější bakteriální membrány